Beyond Traditional Promotion: Digital Marketing Strategies in Education to Enhance Customer Satisfaction - Ria Puspitasari; Sinta Rodiyah; Bambang Sri Anggoro; Sovia Mas Ayu (Journal of Educational Management Research, 2026)
This study aims to analyze the role of digital promotion strategies in enhancing customer satisfaction within educational institutions amid rapid digital transformation. The research employed a Systematic Literature Review (SLR) approach by examining national and international scientific articles indexed in SINTA and Scopus published between 2020 and 2025. Data collection and analysis were conducted through identification, screening, and selection stages using the PRISMA framework to ensure the relevance and quality of the reviewed studies. The findings reveal that the implementation of digital promotion through social media, institutional websites, content marketing, and interactive digital communication significantly contributes to improving customer engagement, institutional image, customer trust, and overall satisfaction in educational services. Digital promotion also enables educational institutions to deliver information more quickly, transparently, and responsively according to the needs of modern society. However, several challenges remain, including limited digital literacy, inadequate human resource capabilities, and increasingly competitive digital environments. Therefore, educational institutions should develop creative, innovative, and customer-oriented digital promotion strategies to strengthen competitiveness and sustain customer satisfaction in the digital era.